The Effect of Irisin on Thyroid Hormone Levels in Chronic Paroxetine-Treated Rats - Ercan, Zubeyde; Dogru, Meryem Sedef; Ertugrul, Nazife Ulker; Yardimci, Ahmet; Canpolat, Sinan (Springernature, 2023)
It is known that serotonin reuptake inhibitors (SSRIs), which are widely used in mood disorders, affect the hypothalamic-pituitary-thyroid axis activity. In this study, we investigated the effect of paroxetine, an SSRI, on thyroid hormone levels in rats. We also examined the role of irisin, a newly discovered potential regulatory hormone for metabolism, on paroxetine-induced changes. A total of 64 Sprague-Dawley female and male rats were randomly divided into four subgroups for each gender and treated as follows: sham-operated control (vehicle), paroxetine (treated with 20 mg/kg paroxetine by oral gavage), irisin (100 ng/kg/day for 28 days with mini-osmotic pumps), and paroxetine + irisin group (n = 8). Serum fasting free triiodothyronine (fT3) and free thyroxine (fT4) levels were measured by automated chemiluminescence method. Serum thyroid-stimulating hormone (TSH) level was determined with enzyme-linked immunosorbent analysis (ELISA). Compared to the sham control group (p < 0.05), the significantly reduced fT4 and TSH serum levels in paroxetine-treated male animals were markedly increased by subcutaneous irisin perfusion. fT3 levels significantly increased in both irisin (4.35 +/- 0.17 pq/mL) and paroxetine + irisin groups (4.51 +/- 0.19 pq/mL) compared to sham control (3.60 +/- 0.23 pq/mL) and paroxetine groups (3.57 +/- 0.12 pq/mL) (p < 0.05). It was observed that serum fT3, fT4, and TSH levels decreased in female animals receiving paroxetine compared to the sham control group. Subcutaneous administration of irisin increased these hormone levels. However, these changes were not statistically significant. These results suggested that irisin may play a role in the mechanism underlying the beneficial effects of exercise in preventing SSRI-related side effects by increasing thyroid hormone levels, which were decreased by paroxetine.
Keywords: Thyroid-stimulating hormone; Triiodothyronine; Thyroxin; Irisin; Paroxetine